Five Design-Sheets : Creative Design and Sketching for Computing and Visualisation /: Creative Design and Sketching for Computing and Visualisation. (2017) - Roberts, Jonathan C; Headleand, Christopher J; Ritsos, Panagiotis D
No abstract available